Function vs. Teleology? - Kořenský, Jan (Bohemica Olomucensia, 2016)
If we understand the Prague functionalism within the meaning of the first paragraph of the Theses then teleology is one-word synonym for dynamic functional structure: means - intent/purpose/function. In this case there is no need to understand teleology as one of the basic concepts of the Prague School. However, if we understand language first of all as immanent structure "conscious of" intentional focusing on the target forms of its structural evolution then teleology is one of the basic concepts of the Prague School. In the first case we can talk about the relation: means - intent/purpose/function, in the second one it is entirely appropriate to talk about the goal.
Keywords: function; teleology; the Prague School